Work Environment and work Engagement of Employees of the Catholic Colleges in the Ilocos Region, Philippines - Abun, Damianus; Magallanes, Theogenia; Acidera, Editha B.; Encarnacion, Mary Joy; Domingcil, Carol U. (Technium Social Sciences Journal, 2021)
The study wanted to determine the effect of the work environment on the work engagement of the employees. To provide a comprehensive view on the topic and established the theories of the study, related literature was reviewed. To gather the data, questionnaires were used. The study used a descriptive assessment and correlational research design. Weighted mean and Pearson r correlation was used to analyse the data. The study found that the bureaucratic environment is high, while, humanistic and entrepreneurial environment is moderate. In terms of work engagement, it is found that employees' work engagement is high. Concerning the correlation between work environment and work engagement, both are significantly correlated. Therefore, the hypothesis of the study is accepted.